Социокультурные аспекты государственной политики информационной безопасности общества - Сайфуллин, К. С. (ХНУРЭ, 2012)
This work is about the modern world of quickly developing information technology and such concept as an information society. The problems connected with information of a society in Ukraine, consequences of this information and a way of its conclusion to morally-etical frameworks are considered.